An approach to verify live NCL applications - Picinin Júnior, Delcino; Farines, Jean-Marie; Koliver, Cristian (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
This paper describes a NCL 3.0 hypermedia application development toolchain which supports the verification of temporal and spatial consistency of NCL applications. In this toolchain, the application is translated into a TSS code and temporal logic formulas are used for checking the desired properties. It is proposed an approach for incremental verification of live NCL applications. The paper illustrates the proposed approach with a case study of a NCL-based interactive TV application.